Topographic Response of Hinterland Basins in Tibet to the India–Asia Convergence: 3D Thermo-Mechanical Modeling - Zhang, Pengpeng; Chen, Lin; Xiao, Wenjiao; Zhang, Ji’en (Frontiers in Earth Science, 2022)
A number of basins have developed in Tibet since the early stage of the India-Asia multiple collision and now they have become integral parts of the Tibetan Plateau. Geophysical and geochemical data reveal that these basins are currently characterized either by strong or weak basements. However, it remains unclear how these hinterland basins evolved during the India-Asia multiple collision and how they affected the post-collisional growth of the Tibetan Plateau. Here we use 3-D thermo-mechanical simulations to investigate the topographic response of a strength-varying hinterland basin imbedded in an orogenic plateau under horizontal compression condition. Our results show that a strong hinterland basin experiences little deformation and develops into a lowland with respect to the surrounding plateau at the early stage of the collision. The lowland gradually shrinks and survives in the interior of the plateau for ~30-40 Myr before merging into the plateau. In contrast, a weak hinterland basin uplifts soon after the initial collision and develops into a highland after ~20 Myr of convergence. Topographic analysis reveals that the strong hinterland basin experiences an evident elevation drop after ~20-30 Myr of convergence, followed by a rapid uplift. After compiling paleoelevation data, we propose that the Tibetan Plateau experienced a four-stage surface uplift, which was characterized by: (1) the Gangdese and Central Watershed highlands isolating three lowlands during the Eocene, (2) the central lowland experiencing an elevation drop of ~2000 m during the Oligocene, (3) the central lowland suffering a rapid uplift and merging into the Tibetan Plateau in the Early Miocene, and (4) the south and north lowlands rising and developing a plateau similar to modern Tibetan Plateau since the Middle Miocene.